Influence of weed and nitrogen management on weed growth, nutrient uptake and yield of wheat (Triticum aestivum) - Prasad, K; Singh, R S (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during winter season of 1991–92 and 1992–93 at Ranchi on weed management in wheat (Triticum aestivum L. emend Fiori & Paol.) under different nitrogen levels. An increase in N level increased the weed density, its dry-matter accumulation and the NPK depletion. Post-emergence application of isoproturon @ 0.75 kg/ha + 2,4-D Na salt @ 0.75 kg/ha gave better control of weeds than their separate application at higher rate of 1.0 kg/ha each in both the seasons. It was comparable with that of weeding by dutch hoe (at 15, 30 and 45 days after sowing) in minimizing the weed density, its dry weight and nutrient depletion by weeds as well as in improving the nutrient uptake and grain yield of wheat. There was no sufficient difference in the grain yields of wheat at 80 and 120 kg N/ha (2826 and 2904 kg/ha). Interaction effects of N levels and weed control methods indicated that sustainable yield of wheat (3625 kg/ha) could be obtained at 80 kg N/ha with post-emergence application of isoproturon @0.75kg/ha+2,4-D Na salt@ 0.75 k/ha.